1997
DOI: 10.1055/s-0038-1656078
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of r-Hirudin Anticoagulation during Cardiopulmonary Bypass – Assessment of the Whole Blood Ecarin Clotting Time

Abstract: SummaryThe use of recombinant ® hirudin as an anticoagulant in performing extracorporeal circulation systems including cardiopulmonary bypass (CPB) devices requires a specific and easy to handle monitoring system. The usefulness of the celite-induced activated clotting time (ACT) and the activated partial thromboplastin time (APTT) for r-hirudin monitoring has been tested on ex vivo blood samples obtained from eight patients treated with r-hirudin during open heart surgery. The very poor relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
0
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(120 citation statements)
references
References 16 publications
1
112
0
7
Order By: Relevance
“…Therefore, the use of ECT, despite limited experience, has been suggested for on-site monitoring of CPB anticoagulation with r-hirudin. 8 Anticoagulation with r-hirudin after cardiac surgery with r-hirudin-based CPB anticoagulation has been reported previously. 9 Based on that report, and because of the short half life of r-hirudin, we started the continuous r-hirudin infusion on the 2nd postoperative hour because chest tube blood loss was < 50 ml·hr -1 although aPTT was prolonged (Table III).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, the use of ECT, despite limited experience, has been suggested for on-site monitoring of CPB anticoagulation with r-hirudin. 8 Anticoagulation with r-hirudin after cardiac surgery with r-hirudin-based CPB anticoagulation has been reported previously. 9 Based on that report, and because of the short half life of r-hirudin, we started the continuous r-hirudin infusion on the 2nd postoperative hour because chest tube blood loss was < 50 ml·hr -1 although aPTT was prolonged (Table III).…”
Section: Discussionmentioning
confidence: 94%
“…A good linear relationship was demonstrated between the hirudin concentration and the ECT but not the ACT values. 8 In addition, ECT values are not influenced by moderate hemodilution. Therefore, the use of ECT, despite limited experience, has been suggested for on-site monitoring of CPB anticoagulation with r-hirudin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Investigators found a strong linear relationship between the ECT values and lepirudin concentrations that ranged from 0.35-5.88 µg/ml (r=0.94), whereas the aPTT demonstrated only weak correlation (r=0.61). Other studies also have found that the ECT correlated better with lepirudin levels and demonstrated less interpatient variability compared with the aPTT 20 or the activated clotting time (ACT). 20,21 In particular, the aPTT curve seems to flatten for lepirudin concentrations above 0.5 µg/ml.…”
mentioning
confidence: 95%
“…Other studies also have found that the ECT correlated better with lepirudin levels and demonstrated less interpatient variability compared with the aPTT 20 or the activated clotting time (ACT). 20,21 In particular, the aPTT curve seems to flatten for lepirudin concentrations above 0.5 µg/ml. 18 Clinical applicability of the ECT tests used in these studies was limited by the fact that it required several manipulations to obtain final results.…”
mentioning
confidence: 95%